ANALISIS GAYA BELAJAR ANAK BINAAN ASRAMA EMAUS KILOMETER 4 NANGA PINOH KABUPATEN MELAWI - Ason Ason (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2021)
Abstract: The purpose of this study was to find out the learning styles of the childrenassisted by the Emmaus Kilometer 4 Nanga Pinoh Dormitory, Melawi Regency. Thisresearch method uses a qualitative descriptive approach. The data collection techniqueused a questionnaire that was compiled referring to three aspects of learning stylemodalities, namely visual, auditory, and kinesthetic. The statements in the questionnairewere compiled based on indicators of each aspect of learning style. The research subjectswere 30 junior and senior high school students as the fostered children of the EmmausDormitory, consisting of 13 boys and 17 girls. Based on the questionnaire data that hasbeen analyzed, it shows that: (1) 30% of students have a tendency with a visual learningstyle; 40% with auditory learning style; and 30% have a kinesthetic learning style. (2)When viewed from the gender, girls tend to have an auditory learning style by 47% and avisual learning style to 35%, while boys have a tendency to a aesthetic learning style by46%. Thus, the learning style tendency of the children under the guidance of the Emmauskilometer 4 Nanga Pinoh dormitory is auditory.Keywords: analysis, learning style, boarding childrenAbstrak: Tujuan penelitian adalah untuk mengetahun gaya belajar anak binaan AsramaEmaus Kilometer 4 Nanga Pinoh Kabupaten Melawi. Metode penelitian ini menggunakanpendekatan diskriptif kualitatif. Teknik pengumpulan data menggunakan angket yangdisusun mengacu pada tiga aspek modalitas gaya belajar yakni visul, auditori, dankinestetik. Pernyataan-pernyataan dalam angket disusun berdasarkan indikator darimasing-masing aspek gaya belajar. Subyek penelitian adalah 30 orang siswa-siswi SMPdan SMA sebagai anak binaan Asrama Emaus, terdiri dari terdiri dari 13 orang laki-lakidan 17 orang perempuan. Berdasarkan data angket yang sudah dianalisis menunjukkanbahwa: (1) 30% siswa memiliki kecenderungan dengan gaya belajar visual; 40% dengan gaya belajar auditori; dan 30 % memiliki gaya belajar kinestetik.(2) Apabila dilihat darijenis kelamin, maka anak perempuan cenderung memiliki gaya belajar auditori sebesar47% dan gaya belajar visual 35%, sedangkan anak laki-laki memiliki kecenderungan gayabelajar konestetik sebesar 46%. Dengan demikian kecenderungan gaya belajar yangdimiliki anak binaan asrama Emaus kilometer 4 Nanga Pinoh adalah auditori. Kata kunci: analisis, gaya belajar, anak asrama